The Transfer of Technology in Students Curricula - Marin-Caihuan, J (IEEE Computer Society, 2019)
This article describes how projects for technological transfer from university research laboratories to enterprises and organizations can offer a stimulating working environment for students to do their practicum as required in many Computer Science Engineering Curricula. A key advantage is that students can effectively work in creative software product development and experience R&D processes. © 1999-2012 IEEE.